Analisis Persepsi Masyarakat Terhadap Pengolahan Minyak Jelantah Skala Rumah Tangga Untuk Perwujudan SDGs - Alifia Putri Darmansyah; Shinfi Wazna Auvaria; Eva Agustina (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The increase in population has an impact on increasing waste, including cooking oil waste known as used cooking oil. This used cooking oil is not always thrown away, but can also be reused. However, improper disposal of waste cooking oil can cause environmental problems. Used cooking oil is a type of waste that can pollute the environment by increasing COD (Chemical Oxygen Demand) and BOD (Biological Oxygen Demand) levels in the water. Apart from that, this oil can also cause an unpleasant odor due to the biological degradation process. Currently, used cooking oil is often thrown directly into the drain. This research was conducted in Wonorejo Village, Surabaya, with data collection methods in the form of questionnaires, field observations and interviews as primary data, as well as a general description of the area and related literature as secondary data. The results of the analysis show that there are variations in views and practices in managing used cooking oil among respondents. The level of public awareness about the importance of managing used cooking oil to support the zero waste concept varies. The majority of respondents (64%) stated that the main responsibility for managing used cooking oil lies with the users themselves.